Globalisasi dan Tenaga Kerja: Internalisasi Norma Sertifikasi Tenaga Kerja Pariwisata di Indonesia - Soeharto, Dyah Nurnaningtyas (Department of International Relations, Brawijaya University, 2021)
Tourism is one of ASEAN's economic leading sectors. In order to improve the quality and mobility of the tourism professional workforce, ASEAN countries established ASEAN-MRA TP as the regional standard form of certification. The implementation of the ASEAN-MRA TP encourages Indonesian workers to obtain certification as proof of competence. However, the Indonesian tourism professional workforce rate is low, compared to the total tourism workforce in general. The culture of personal networking that deeply rooted in the tourism workforce is hampering Indonesian effort in implementing the ASEAN-MRA TP certification norm. By using Cortell A.P and Davis J's theory of domestic salience, this study aims to analyze the government's efforts to internalize the ASEAN-MRA TP certification norms to the domestic level, with the challenges of existing domestic cultures. There are 4 strategic actions taken, domestic institution, domestic interest, rhetoric and socialization forces. Keywords : Certification, ASEAN MRA-TP, Indonesia tourism professional workers, The culture of personal networking